Utilization of Landsat 8 Imagery for Analyzing Land Surface Temperature in Sumbawa Regency from 2018 to 2022 Using Google Earth Engine - Meilinda Fauzi; Wiwit Febrianti; Elsa Amini; Nuzla Af'idatur Robbaniyyah (Program Studi Matematika, 2026)
This study aims to analyze the land surface temperature in Sumbawa Regency from 2018 to 2022 using Landsat 8 imagery and the Google Earth Engine (GEE) platform. The surface temperature data was obtained from the Landsat 8 image collection with a spatial resolution of 1 km and a temporal resolution of 8 days. The Split Window Algorithm was used to calculate the land surface temperature based on thermal infrared data. The analysis process included image acquisition, selection of daytime temperature bands, and conversion of temperature from Kelvin to Celsius. The results showed variations in the average land surface temperature in Sumbawa Regency over the five-year period, with a decreasing temperature trend in certain years, possibly related to climatic factors and the increase in green open spaces. These data can be used to support natural resource management and mitigate the impacts of climate change in the region. This study also emphasizes the importance of utilizing remote sensing technology and cloud computing platforms for efficient and integrated geospatial analysis.